2016
DOI: 10.1371/journal.pone.0160039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long Non-Coding RNA HOTAIR Polymorphisms with Cervical Cancer Risk in a Chinese Population

Abstract: Long non-coding RNAs (lncRNAs), HOTAIR has been reported to be upregulated in cervical cancer development and progression. However, SNPs (single nucleotide polymorphisms) in the lncRNAs and their associations with cervical cancer susceptibility have not been reported. In the current study, we hypothesized that SNPs within the lncRNA HOTAIR may influence the risk of cervical cancer. We performed a case-control study including 510 cervical cancer patients (cases) and 713 cancer-free individuals (controls) to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 43 publications
1
68
0
Order By: Relevance
“…Similar results were observed in an animal study in which propofol inhibited tumor size and cell viability and promoted cell apoptosis via the HOTAIR-mediated inhibition of the mTOR/ p70S6K pathway in CaCx [98]. In the evaluation of the association between 3 haplotypetagging SNPs (rs920778, rs1899663 and rs4759314) in HOTAIR and the risk of CaCx, the SNP rs920778 in the intronic enhancer of HOTAIR was strongly associated with CaCx, and high HOTAIR expression was associated with the risk-associated allele T [99]; these results confirmed that functional SNP rs920778 regulated HOTAIR expression and might ultimately influence the predisposition for CaCx [99]. In addition, 1209 cases of CaCx and 1348 controls were enrolled in a study using the TaqMan allelic discrimination method and the Cancer Genome Atlas (TCGA) database for analysis of allele-specific HOTAIR expression.…”
Section: Hotair In Cervical Cancermentioning
confidence: 98%
“…Similar results were observed in an animal study in which propofol inhibited tumor size and cell viability and promoted cell apoptosis via the HOTAIR-mediated inhibition of the mTOR/ p70S6K pathway in CaCx [98]. In the evaluation of the association between 3 haplotypetagging SNPs (rs920778, rs1899663 and rs4759314) in HOTAIR and the risk of CaCx, the SNP rs920778 in the intronic enhancer of HOTAIR was strongly associated with CaCx, and high HOTAIR expression was associated with the risk-associated allele T [99]; these results confirmed that functional SNP rs920778 regulated HOTAIR expression and might ultimately influence the predisposition for CaCx [99]. In addition, 1209 cases of CaCx and 1348 controls were enrolled in a study using the TaqMan allelic discrimination method and the Cancer Genome Atlas (TCGA) database for analysis of allele-specific HOTAIR expression.…”
Section: Hotair In Cervical Cancermentioning
confidence: 98%
“…Several studies previously investigated the relationships between these 3 SNPs and cancer risks. The rs920778 A>G polymorphism, located in the intronic enhancer of HOTAIR , had a genotype‐specific effect on HOTAIR expression, and was associated with breast cancer and cervical cancer . The rs4759314 A>G polymorphism, located in TFBS, was associated with gastric cancer and EOC, and the rs7958904 G>C polymorphism, located in exon 6 of HOTAIR , was associated with colorectal cancer, EOC, osteosarcoma, and cervical cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The rs920778 A>G polymorphism, located in the intronic enhancer of HOTAIR, 34 had a genotype-specific effect on HOTAIR expression, 34 and was associated with breast cancer 38,65 and cervical cancer. 66 The rs4759314 A>G polymorphism, located in TFBS, was associated with gastric cancer and EOC, 39 and the rs7958904 G>C polymorphism, located in exon 6 of HOTAIR, 67 was associated with colorectal cancer, EOC, osteosarcoma, 39 and cervical cancer. 67 Along with the previous reports cited above, the results of the current study suggest that the genetic variation of HOTAIR is complex and depends on cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that rs920778 was associated with the development of hepatocellular carcinoma. The function of rs920778 on HOTAIR was confirmed in other cancers, including esophageal squamous cell carcinoma [19], gastric cancer [30], colorectal cancer [21], and breast cancer [31]. Moreover, Zhang et al reported that SNP rs920778 in HOTAIR may affect the expression of HOTAIR, which may be an underlying mechanism by which the SNP affects tumor susceptibility [20].…”
Section: Discussionmentioning
confidence: 99%
“…Based on published association studies, three HOTAIR HapMap tagSNPs (htSNP) (rs1899663, rs920778, and rs4759314) were selected and genotyped as described previously [19]. SNP genotyping was performed without knowledge of the patient or control status.…”
Section: Methodsmentioning
confidence: 99%